The Bacteriophage lambdaDNA packaging enzyme: Identification of four structural domains of the gpNu1 subunit using limited proteolysis - ARAYA,PAMELA (Sociedad de Biología de Chile, 2001)
Lambda DNA terminase, the enzyme that cleaves virion-length chromosomes from multigenomic concatemers and packages them into the bacteriophage head, is composed of two subunits, gpNu1 and gpA. Direct determination of the structure of gpNu1, the smaller subunit, has not been possible because of its insolubility in aqueous solutions. Therefore, to identify smaller and potentially water-soluble domains of gpNu1, we analyzed the nature of the products obtained by limited digestion of the protein with several proteases. The gpNu1 subunit was obtained from E.coli cells transfected with the plasmid pH6-Nu1 that overproduces the protein. Incubation of gpNu1 solubized in 2.5 M guanidinium chloride with chymotrypsin resulted in the formation of at least eight discrete protein bands, while treatment with endoproteinase glu-C and bromelain yielded three and one major bands, respectively. The peptides generated by digestion with the various proteases were separated by two-dimensional gel electrophoresis and transferred to Immobilon membranes. Amino acid sequencing of the peptides allowed for the precise assignment of their N-terminal amino acid, while their estimated molecular weights permitted the identification of their C-terminal ends. The results reveal that in the presence of 2.5 M guanidinium chloride, gpNu1 is partially folded in at least four distinct structural domains that correspond to functional domains as determined by previously reported genetic experiments. This information is key to design new plasmids to overproduce these domains for further structural analysis.